Bringing the Audio Visual Learning Media to Enhance the Cognitive Learning Outcomes: A Case Study on Cattari Ariya Saccani Chapter of Buddhist Religious Lesson Material at School - Agus Setiawan; Ayu Andriyaningsih; Komang Sutawan; susanto Susanto; Arya Sura Pratama; Karsinah Karsinah; Rini Kasrah (Universitas Sebelas Maret, 2024)
The variables of audio-visual learning media with cognitive learning outcomes were examined to determine the strength and magnitude of the influence. The problem among students was that using media made them understand the material better if there were pictures. It is more enjoyable to use media because of examples of the material. The approach used in this research is quantitative involving 34 respondents with a survey method. The study was conducted in junior high schools with student respondents. Before conducting a simple linear regression test, the initial stage is tested with a validity test and then a reliability test. This result shows that the significance value is less than 0.05 and the R square value is 0.499. This means that audio-visual-based learning media affects cognitive learning outcomes with a nominal amount of 49.9%, as well as other influencing factors by 50.1%.